Tinjauan Beberapa Metode Perencanaan Pembuatan Jalan Hutan Untuk Logging - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT In general, there are three methods to plan transportation network in forest management, namely Matthews, Ulf Sundberg and Von Sagebaden methods. This study tried to understand the strength and the deficiensies of each method as applied in the field. The study was conducted at PT Hutan Kintap, South Kalimantan. Criteria used to justify the method order were road construction and skidding cost. Road density and road spacing were calculated using those two data. The study concluded that the Optimum Road Density based on Von Sagebaden method was better than the other two methods, because it introduced the area correction factor skidding and transporting